Harvesting oil palm at right time fetches more return - Kumar, K Sunil; Rahena, S N; Murugesan, P (Indian Horticulture, 2019)
Oil palm is the highest edible oil-producing crop. It produces 4-6 million tonnes of palm oil and 0.4-0.6 million tonnes of palm kernel oil which is fourfold higher than other oilseed crops. Hence, its cultivation is promoted to reduce the gap between edible oil demand and availability in our country. The quality and quantity of oil recovered from oil palm depends on the way fresh fruit bunches are harvested and processed. The stage of maturity at harvesting is one of the main factors deciding oil recovery and economics of the crop. A week before harvesting, oil formation reaches only 80% and hence, if under ripe fruits are harvested, there is a loss of oil. In case of over ripe bunches, oil recovery is reduced on account of fruit shedding. Also, the quality of oil deteriorates due to accumulation of free fatty acids. Hence, correct stage of harvesting is most important. This could be achieved by counting numbers of fruits that are shed, change in colour of fruits or fruit texture assessment. First two are more commonly followed to arrive at correct maturity of harvesting. Presently in India, a minimum of 4% recovery gap is reported, which is equivalent to 26,000 tonnes of crude palm oil as per present production. This could be saved if correct harvesting and processing techniques are adopted.